The human foamy virus pol gene is expressed as a Pro-Pol polyprotein and not as a Gag-Pol fusion protein. - Löchelt, M (1996)
It has been reported recently that the human foamy virus (HFV) Pol polyprotein of 120 kDa is synthesized in the absence of the active HFV aspartic protease. To gain more information on how the 120-kDa Pro-Pol protein is synthesized, mutant HFV genomes were constructed and the resulting proviruses were analyzed with respect to HFV pol expression and infectivity. HFV proviruses that contain termination codons in the nucleocapsid domain of gag and thus lack a gag-pol overlap region assumed to be required for translational frameshifting, nevertheless expressed the 120-kDa Pro-Pol precursor, the 80-kDa reverse transcriptase/RNase H, and a 40-kDa integrase in amounts similar to those observed for wild-type genomes. Since a Gag-independent expression of authentic Pol proteins was detectable in cells transfected with eukaryotic HFV pol expression plasmids, the data indicate that the HFV Pol precursor of 120 kDa is expressed independently of Gag by a mechanism that does not rely on ribosomal frameshifting, since the postulated HFV Gag-Pol protein of 190 kDa was not detectable under the conditions used. Furthermore, replacement of the Met residue by Thr at position 9 in pol within the gag-pol overlap region resulted in strongly reduced HFV Pol polyprotein expression and infectivity of the resulting proviruses. This Met residue of pol conserved in foamy virus sequences is the likely candidate for translational initiation of the 120-kDa Pro-Pol polyprotein. trans complementation of the HFV mutant with the Met-to-Thr substitution in the pol gene by a eukaryotic plasmid that expressed the HFV Pro-Pol protein resulted in partial recovery of infectivity. When HFV pol was fused in frame to gag, an engineered 190-kDa Gag-Pol fusion protein was formed and the enzymatic activity of the HFV protease was partially retained. The results imply that HFV is the first retrovirus that expresses a Pol polyprotein without formation of a Gag-Pol fusion protein.